2021
DOI: 10.3390/cancers13040716
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations and Health-Related Quality of Life (HRQOL): A Genome-Wide Study Approach

Abstract: Health-related quality of life (HRQOL) is an important prognostic patient-reported outcome in oncology. Because prior studies suggest that HRQOL is, in part, heritable, we performed a GWAS to elucidate genetic factors associated with HRQOL in breast cancer survivors. Physical and mental HRQOL were measured via paper surveys that included the PROMIS-10 physical and mental health domain scales in 1442 breast cancer survivors participating in the Mayo Clinic Breast Disease Registry (MCBDR). In multivariable regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
0
1
Order By: Relevance
“…Candidate gene studies on cancer have reported that some genetic variations are associated with fatigue, pain, loneliness, anxiety, sleep, alcohol consumption, and smoking [18][19][20][21][22][23][24] . On the contrary, large cohort studies failed to find genetic variations significantly associated with QOL and could not replicate previously reported candidate gene associations [25][26][27][28] .…”
Section: Discussioncontrasting
confidence: 75%
“…Candidate gene studies on cancer have reported that some genetic variations are associated with fatigue, pain, loneliness, anxiety, sleep, alcohol consumption, and smoking [18][19][20][21][22][23][24] . On the contrary, large cohort studies failed to find genetic variations significantly associated with QOL and could not replicate previously reported candidate gene associations [25][26][27][28] .…”
Section: Discussioncontrasting
confidence: 75%